37 Hypoxic Challenge Testing in Infants; who is recommended to fly with supplemental oxygen?. (30th November 2020) - Riley, Mollie; Fettes, Emma; Laverty, Aidan; Aurora, Paul
Abstract : Infants with a history of neonatal chronic respiratory problems may demonstrate hypoxaemia when at in-flight oxygen levels, despite normal sea-level oxygen requirements. The British Thoracic Society recommend these infants have hypoxic challenge testing (HCT) before air travel, SpO2 <85% is recommended as a threshold below which in-flight oxygen is required and 'paediatrician discretion should be used when SpO2 between 85–90% and, where there is doubt, the doctor should err on the side of caution.' Aim: To establish how many infants fell into each of the threshold categories during HCT; SpO2 <85%, >90%, 85–90% and which of these patients were recommended to fly ± supplemental oxygen (suppO2 ). Methods: Our HCT protocol for infants is 20 minutes in 15% FiO2 within a body plethysmograph. SpO2 is monitored throughout and suppO2 administered via nasal cannula if SpO2 < 85%. If after 20 minutes SpO2 has remained >85% but <90% then suppO2 is titrated for 5 minutes. We reviewed data collected from infants (aged < 1 year) whom had HCT between March 2017- January 2020. Results: Data collected from 65 infants, median age 27.6 weeks (range 5 to 51.6), 37 were male. None were receiving suppO2 in room air prior to testing; all had baseline SpO2 ≥96%. In 40 infants, SpO2 did not dip to <90%. SpO2 dropped to <85% in 16 infants, requiring administration of suppO2 . 9 infants required extended protocol due to SpO2 85–90%. SuppO2 corrected SpO2 in all to baseline levels. In the 85–90% category, all 9 infants were advised by their clinician to use suppO2 for air travel.The flight times in this subgroup ranged from 90 to 450 minutes. Conclusion: Infants with baseline SpO2 ≥96% may still exhibit SpO2 desaturation during HCT. We found all paediatricians recommended in-flight oxygen for infants with HCT SpO2 <90% regardless of flight duration.